PEMANFAATAN MASTER KOI BOT DALAM PEMASARAN IKAN KOI DENGAN METODE LELANG ONLINE - Mustofa, Romy Faisal; Gustaman, Randy Fadilah; Khoerunisa, Nisa; Rosita, Lilis; Marlyono, Setio Galih (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Marketing Koi fish has become a rapidly growing trend among hobbyists. One effective method in increasing the selling value of Koi fish is through auctions. This article discusses the use of Master Koi Bot, a digital platform that connects Koi fish sellers and buyers, in facilitating the auction process. This approach not only allows sellers to reach a wider audience, but also provides a transparent and secure experience for buyers. By using this technology, marketing koi fish through the auction method can be more efficient and profitable for all parties involved. The main object of this community service focuses on marketing through online auctions through Master Koi Bot ornamental fish products at Bagja Buana and Karyamas business institutions so that they can be utilized by the community in increasing marketing effectiveness. By marketing through online auctions in the Master Koi Bot application, it is hoped that it will save more costs and open up the market widely by utilizing the rapid development of information technology and communication today. There are many platforms that can be used as marketing opportunities such as utilizing social media, websites, YouTube, e-marketplace applications and so on. The main problems of ornamental fish farmer groups in Kondangjajar Village, Cijulang District, Pangandaran Regency are a) Effectiveness of Master Koi Bot Utilization in Koi Fish Marketing through Auction Method; b) Buyer Perception and Enthusiasm towards the Utilization of Master Koi Bot in Auction Method; c) Influence of Quality and Quantity of Koi Fish Offered on Auction Results with the Use of Master Koi Bot.